Digital literacy: a narrative review of scientific literature related to elderly (Jóvenes en la Ciencia, 2026)
This narrative review aims to explore the current state of digital literacy among older adults in Mexico and how various cognitive, emotional, social, and structural factors influence their learning and use of digital technologies. Through an analysis of academic literature published between 2015 and 2025, it addresses both the advances in digital inclusion among this population and the main barriers they face.The findings reveal that, although there are some institutional efforts to reduce the digital divide, digital literacy remains limited, particularly in rural areas and communities with fewer resources. In addition, factors such as technological anxiety, lack of self-efficacy, and ageist attitudes hinder the learning process and the adoption of new technologies.The importance of designing educational programs and intervention strategies tailored to the cognitive and emotional characteristics of older adults is emphasized. These should encourage practical and meaningful learning that promotes autonomy and social inclusion among older adults.Finally, the review highlights gaps in research, pointing to the need for more in-depth studies that address digital literacy from a longitudinal perspective and explore its impact on the mental health and social well-being of older adults in the long term.